Enhanced soil attributes, yield and fruit quality of Medjool date palm (Phoenix dactylifera L.) in response to filter mud/cake for drylands sustainability - Atef Abo-Ogiala; Abdel-Moety Salama; Mohamed S. Aboryia; Ahmed M. Fikry; Nazih Y. Rebouh; Mohamed S. Shokr; Naglaa Khalafallah (PLoS ONE, 2026)
Soils of drylands in arid and semiarid conditions need developing approaches to improve the holding capacity of water and nutrients to avoid desertification. In this study, we examine the characteristics of filter mud/cake under the intended conditions and verify the additional value of employing it as a byproduct of the sugarcane industry, avoiding its negative impacts on the environment. This was accomplished in two prosperous seasons in 2022 and 2023 by using uniform Medjool date palms ( Phoenix dactylifera L.) that were ancient, vigorous, fruiting, and healthy at a private farm in Dakhla Oasis, New Valley Governorate, Egypt. The application of filter mud as a soil amendment significantly led to better results in all parameters under investigation, i.e., soil attributes, yield parameters, and fruit quality, compared to the additive of animal and poultry manure used separately. However, the results suggested applying filter mud mixed to poultry manure (T6), that showed better results compared to other treatments, i.e., water content at field capacity (WFC) were 12.58 and 12.59%, whereas NPK content in soil were 35.23 and 35.25 mg/kg N, 5.33 and 5.37 mg/kg P, 61.21 and 61.18 mg/kg K in both seasons 2022 and 2023, respectively. Moreover, T6 treatment showed the best results of yield per date palm tree, i.e., 65 and 66 Kg with the highest fruit quality indicators, i.e., 8 and 8.1 cm fruit length, 2.7 and 2.8 cm fruit diameter in both seasons as respectively. The study presented filter mud as promising application for soil amendment in arid and semiarid conditions with direct contribution to key Sustainable Development Goals (SDGs). Subsequently, enhancing soil health and sustainable agriculture (SDG 2: Zero Hunger), fostering green innovation in by-product valorization (SDG 9: Industry, Innovation, and Infrastructure), and promoting the sustainable management and reduction of industrial waste (SDG 12: Responsible Consumption and Production).